Relationship between Motivation, Knowledge, and Availability with the Use of Personal Protective Equipment - Yogi Adiputro (The Indonesian Journal of Occupational Safety and Health, 2019)
Introduction: Clinical laboratories are a kind of workplace that must be designed in strict compliance with occupational health and safety standards to create a safe work environment. Fatal work accidents can inflict injuries caused by improper use of equipment, poisoning due to chemical substances in clinical laboratories, and transmission of dangerous diseases. Methods: This is an observational research with a cross sectional approach. The population of this study was 15 health analysts in the X Regional Clinical Laboratory of East Java. The research used total sampling method, carried out from July to September 2018. The dependent variable is the use of PPE and the independent variables are the lack of control and the basic causes. Data were analyzed using Chi square and Spearman correlation tests. Results: 53.3% of the employees of X Regional Clinical Laboratory of East Java use PPE accordingly. There is a strong relationship between knowledge and the use of PPE (r= 0.607). There is a strong correlation between the motivation and the use of PPE (r= 0.600). There is a strong relationship between the availability of PPE and the use of PPE (r = 0.756). Conclusion: There is a strong relationship between knowledge, motivation, and availability of PPE with the use of PPE.Keywords: knowledge, motivation, personal protective equipment